IMPLEMENTASI METODE BATUNG BINGAR DALAM PEMBERANTASAN BUTA AKSARA - Friska Indria Nora; Jubaidah Hasibuan; Nurul Aulia Sukma; Rizki Khairunnisa; Irna Nursaidah Telaumbanua (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
This study aims to determine the impact of the application of the Batung Bingar method in an effort to eradicate illiteracy on Jl. Gurilla, Medan Tembung District, Medan City, North Sumatra. Batung Bingar is a method that combines reading, writing, arithmetic, speaking, and listening which is believed to be easier in the learning process. Because in this method, learning citizens can benefit in every given realm. These realms complement and have a relationship with each other. The research method used is a qualitative research method. Data collection techniques used by using interview and observation techniques. The research on the application of the Batung Bingar method was carried out on 4 learning residents who were illiterate in Jalan Gurilla. Where the tutor applies the methods of reading, writing, counting, speaking, and listening well so that the learning residents are able to memorize letters and are able to read even though they are still stammering, and are able to hear and absorb every provision of learning material provided and help residents learn to be smart. in counting and writing.